(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This article analyzes the metaphorical expression of the woman’s image based on a linguocognitive approach. The study examines the role of metaphor in human thinking, its conceptual nature, and the features of the expression of the woman’s image in various semantic and cultural models. In particular, the concept of woman is illuminated through metaphorical structures such as "mother", "element of nature", "embodiment of beauty". The article also analyzes the inextricable connection of these metaphors with gender perceptions and cultural stereotypes in society. The results of the study serve to determine the place of the woman’s image in the system of language and thought.